The Effect of Peanut Ball on the Duration of Labor in Mothers in the First Stage of Active Labor - Anggraeniy, Mayang Eustacia; Kundarti, Finta isti; Titisari, Ira; Rahayu, Dwi Estuning (EMBRIO: Jurnal Kebidanan, 2025)
Indonesia's maternal mortality rate (MMR) and infant mortality rate (IMR) remain relatively high, partly due to prolonged labor that is not managed effectively managed. The peanut ball technique is a non-pharmacological alternative to accelerate labor. This study aims to assess the effect of the peanut ball on labor duration among mothers delivering in the active phase of the first stage. The study employed a quasi-experimental pretest–posttest control-group design. Sixty participants were split into two groups: 30 in the intervention group and 30 in the control group. The intervention group used the peanut ball technique for 120 minutes, while the control group received standard delivery care. Consecutive sampling was used. The study was conducted at Aura Syifa Hospital, Baptist Hospital, and Nirmala Hospital in Kediri. Data were analyzed using the Mann–Whitney test. The results showed that the average labor duration in the intervention group was 150.2 plus minus 60.779 minutes, and the control group was 199.5 plus minus 76.191 minutes, with a p-value of 0.000 (p less than 0.05). The peanut ball technique has been proven effective in accelerating labor. This technique can be implemented as a non-pharmacological intervention in obstetric care.